2008
DOI: 10.1536/ihj.49.605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Losartan and Carvedilol on Attenuating Inflammatory and Oxidative Response and Preserving Energy Transcription Factors and Left Ventricular Function in Dilated Cardiomyopathy Rats

Abstract: SUMMARYWe compared the effects of losartan and carvedilol on preserving left ventricular (LV) function in an experimental model of dilated cardiomyopathy (DCM) and examined the mechanisms of their pharmacological effects. The rats were divided into group 1 (normal control), group 2 (DCM), group 3 (DCM plus carvedilol 8 mg/kg/day bid orally), and group 4 (DCM plus losartan 20 mg/kg/day orally). All rats were sacrificed on day 90 following DCM induction. The results indicated that connexin43 protein expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In the heart, endogenous ET‐1, which is locally generated and secreted by cardiomyocytes, may contribute to cardiac hypertrophy via an autocrine/paracrine fashion . The role of ET‐1 in adverse myocardial remodeling has been reported by various studies . In the present study, supplementation of MLD has shown significant suppressive effect on the ET‐1 levels in the myocardium of the DCM rats.…”
Section: Discussionsupporting
confidence: 56%
“…In the heart, endogenous ET‐1, which is locally generated and secreted by cardiomyocytes, may contribute to cardiac hypertrophy via an autocrine/paracrine fashion . The role of ET‐1 in adverse myocardial remodeling has been reported by various studies . In the present study, supplementation of MLD has shown significant suppressive effect on the ET‐1 levels in the myocardium of the DCM rats.…”
Section: Discussionsupporting
confidence: 56%
“…The activation of AT1 receptors localized on these inflammatory cells [171,172] may increase adhesion of monocytic cells to the endothelium [173,174]. As a result, application of losartan attenuates myocardial inflammation by the inhibition of proinflammatory role of AT1 receptor activation [175]. Furthermore, losartan may block the subsequent interaction among inflammation, fibrosis, and cell death [176].…”
Section: Losartan and The Cardiac Rasmentioning
confidence: 99%
“…In these reports, low dose carvedilol could improve the cardiac function and reduced the atrial natriuretic peptide, whose level in the plasma is related to the severity of HF [29]. In similar animal model, carvedilol is comparable to losartan in attenuating inflammation, oxidative response, myocardial fibrosis and apoptosis, as well as in preserving energy transcription factors and left ventricular (LV) function [30]. …”
Section: Carvedilol In Dilated Cardiomyopathymentioning
confidence: 99%
“…In DCM, regardless of its etiology, superoxide production and pro-inflammatory cytokines are known to be increased [56]. Carvedilol therapy can significantly preserve LV function, up-regulated Cx43 expression in cardiomyocytes and down-regulate cellular apoptosis in an animal model of DCM by at least partly through the attenuation of pro-inflammatory cytokines and induction of anti-inflammatory markers including IL-10 and endothelial nitric oxide syntheses [30]. A report which has been further investigated the beneficial effect of carvedilol in both ischemic and non-ischemic DCM clarified that carvedilol suppresses the plasma levels of TNF-α and IL-6 in both ischemic and non-ischemic DCM patients.…”
Section: Carvedilol Other Than Its Traditional Propertiesmentioning
confidence: 99%